The factors associated with teachers' job satisfaction and their impacts on students' achievement: A review (2010-2021) - Hoque, Kazi Enamul (Springer Nature, 2023)
The success of any educational organization depends heavily on the effectiveness of its teachers, who are tasked with transferring knowledge, supervising students, and enhancing the standard of instruction. Teachers' job satisfaction has a significant impact on the lessons they teach since they are directly involved in transferring knowledge to students. In order to determine the effect of teachers' job satisfaction (TJS) on students' accomplishments, the researchers sought to analyze the empirical studies conducted over the previous 12 years (SA). To determine the characteristics that link to instructors' job satisfaction and their effect on students' achievement, thirty-two empirical studies were examined. The analysis of world-wide empirical research findings shows four types of results: (i) In some countries, teachers' job satisfaction is low, but students' achievement is high (Shanghai, China, South Korea, Japan, Singapore) (ii) In some countries, teacher job satisfaction is high, but student achievement is low (Mexico, Malaysia, Chile, Italy). (iii) In some countries, teachers' job satisfaction is high, and so is student achievement (Finland, Alberta, Canada, Australia). (iv) In some countries, teacher job satisfaction is low, which has a negative impact on student achievement (Bulgaria, Brazil, Russia). In sum, irrespective of countries, highly satisfied teachers give their best to their students' success, not only by imparting knowledge but also by giving extra attention to ensure the better achievement of each student. The review of this study makes it even more worthwhile to reflect on the need to avoid stereotypical considerations and assessments of any objective presentation of the phenomenon and to reflect more deeply on the need to assess the validity of the relationship study.